2016
DOI: 10.1097/ijg.0000000000000275
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness and Open-Angle Glaucoma: A Meta-Analysis and Systematic Review

Abstract: Our meta-analysis found no significant difference in the choroidal thickness both under the fovea and around the optic nerve head between OAG patients and controls. On the basis of the anatomic features of blood supply in optic nerve head, it is plausible that the choroidal thickness is not an appropriate parameter to evaluate the damage of OAG, and choroidal thinning may not be an important component of glaucomatous optic neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 53 publications
1
29
1
Order By: Relevance
“…Using enhanced depth imaging optical coherence tomography (EDI-OCT), other authors found no significant differences in choroidal thickness around the optic nerve between glaucoma patients and healthy controls. [23,24] However, our results indicate that ONH oxygen saturation in choroidal circulation decreases significantly with increasing RNFLT. We speculated that the choroidal oxygen saturation values obtained in this study are related to retinal transmission function rather than glaucomatous damage as determined by RNFLT.…”
Section: Discussionmentioning
confidence: 57%
“…Using enhanced depth imaging optical coherence tomography (EDI-OCT), other authors found no significant differences in choroidal thickness around the optic nerve between glaucoma patients and healthy controls. [23,24] However, our results indicate that ONH oxygen saturation in choroidal circulation decreases significantly with increasing RNFLT. We speculated that the choroidal oxygen saturation values obtained in this study are related to retinal transmission function rather than glaucomatous damage as determined by RNFLT.…”
Section: Discussionmentioning
confidence: 57%
“…[13,21,34] However, analyzing the 6 peripapillary sectors separately showed that there was a significant difference in the temporal peripapillary choroidal area between normal and 10° tubular visual field POAG eyes. In patients with POAG, the high IOP may put pressure on the blood supply of the retina, leading to ischemia of the nerve fiber and glaucomatous damage.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies indicated no significant difference in the mean peripapillary choroidal thickness between normal and POAG eyes. [1315] However, those studies did not divide the patients with POAG into subgroups according to the visual field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, due to choroid changes in high myopia (21), patients with a refractive error greater than 6 diopters were excluded. Glaucoma was not considered an exclusion criterion as an association between NPH and normal tension glaucoma (NTG) is postulated in previous studies (12) and the presence of glaucoma as well as the degree of glaucomatous damage does not influence choroid thickness parameters (2224). …”
Section: Methodsmentioning
confidence: 99%